PERSEPSI MAHASISWA AKUNTANSI DAN HUKUM UNIVERSITAS SLAMET RIYADI SURAKARTA MENGENAI ETIKA TAX EVASION - Melati Pesona Putri; Fadjar Harimurti; Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This study aims to analyze the perceptions of Accounting students and Law students on the ethics of tax evasion, as well as analyzing the differences in the perception of tax evasion ethics between Accounting students and Law School students Slamet Riyadi Surakarta. Data collection techniques using a questionnaire. The instrument testing uses validity and reliability tests. The data analysis technique used is the F test and the t test of two independent samples (Independent t-Test). The calculation results show that accounting students' perceptions of majority tax evasion are "sometimes ethical". The perception of tax evasion ethics by Law students mostly states it is always ethical. There is a difference in perception between Accounting students and Law students towards tax evasion.